2018
DOI: 10.3390/ijms19041097
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Mediators for Cigarette Smoking Induced Atherosclerosis

Abstract: Smoking increases the risk of atherosclerosis-related events, such as myocardial infarction and ischemic stroke. Recent studies have examined the expression levels of altered microRNAs (miRNAs) in various diseases. The profiles of tissue miRNAs can be potentially used in diagnosis or prognosis. However, there are limited studies on miRNAs following exposure to cigarette smoke (CS). The present study was designed to dissect the effects and cellular/molecular mechanisms of CS-induced atherosclerogenesis. Apolipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Specifically, the expression of mmu-miR-21a-5p, mmu-miR-147-3p, mmu-miR-449a-5p, and mmu-miR-703 was deregulated in the lungs of mice exposed to multi-walled carbon nanotubes [24] and mmu-miR-342-3p in mice exposed to nano-TiO2 particles [25]. The deregulation of the miRNAs observed in our study was further found in the lungs of mice after cigarette smoke exposure (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-146b-5p, mmu-miR-155-5p, mmu-miR-342-3p, mmu-miR-449a-5p, mmu-miR-489-3p, and mmu-miR-672-5p) [26], in mice with cigarette smoke induced atherosclerosis (mmu-miR-21a-5p and mmu-miR-155-5p) [27], in the lungs of mice after radon inhalation (mmu-miR-21a-3p, mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-1298-5p, mmu-miR-6972-5p, and mmu-miR-703) [28], in mice with lung tumors (mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-223-3p, and mmu-miR-1298-5p) [29][30][31], in an ovalbumin-induced asthma mouse model (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-155-5p, mmu-miR-223-3p, and mmu-miR-451a) [32], and in mice with pneumonia and influenza infections (mmu-miR-21a-5p, mmu-miR-144-5p, mmu-miR-155-5p, and mmu-miR-223-3p) [33][34][35]. This overall suggests that the inhalation of CuO NPs induces a similar response as the above-mentioned adverse conditions and therefore likely has negative effects on the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the expression of mmu-miR-21a-5p, mmu-miR-147-3p, mmu-miR-449a-5p, and mmu-miR-703 was deregulated in the lungs of mice exposed to multi-walled carbon nanotubes [24] and mmu-miR-342-3p in mice exposed to nano-TiO2 particles [25]. The deregulation of the miRNAs observed in our study was further found in the lungs of mice after cigarette smoke exposure (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-146b-5p, mmu-miR-155-5p, mmu-miR-342-3p, mmu-miR-449a-5p, mmu-miR-489-3p, and mmu-miR-672-5p) [26], in mice with cigarette smoke induced atherosclerosis (mmu-miR-21a-5p and mmu-miR-155-5p) [27], in the lungs of mice after radon inhalation (mmu-miR-21a-3p, mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-1298-5p, mmu-miR-6972-5p, and mmu-miR-703) [28], in mice with lung tumors (mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-223-3p, and mmu-miR-1298-5p) [29][30][31], in an ovalbumin-induced asthma mouse model (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-155-5p, mmu-miR-223-3p, and mmu-miR-451a) [32], and in mice with pneumonia and influenza infections (mmu-miR-21a-5p, mmu-miR-144-5p, mmu-miR-155-5p, and mmu-miR-223-3p) [33][34][35]. This overall suggests that the inhalation of CuO NPs induces a similar response as the above-mentioned adverse conditions and therefore likely has negative effects on the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were exposed to CS at low (2 puffs/min for 40 min/day) or high dose (2 puffs/min for 120 min/day) (n = 7 per group) for 5 days a week for 2 months. The CS inhalation was conducted using unfiltered research cigarette 3R4F (Tabacco Health Research Institute, Kentucky University, Lexington, KY) and the Tabacco Smoke Inhalation Experiment System for small animals (Model SIS-CS; Shibata Scientific Technology, Tokyo, Japan) 44 . The smoke generator automatically generated CS by setting the volume of the syringe pump and the number of puffs per minutes.…”
Section: Methodsmentioning
confidence: 99%
“…We found a lower mRNA expression of LXRa, PPARa, and ABCA1/G1 followed by TC accumulation in the NNK/CS group compared with the control group in lungs. Although the mechanism(s) underlying lower expression of PPARa, LXRa, and its target genes in lungs after NNK/CS exposure remains unclear, previous studies reported an increased expression of micro-RNAs (e.g., miRNA-21, miRNA-155, and miRNA-20), which target PPARa/LXRa and ABCA1/G1, after CS exposure (44,45). These findings could help us to explain the downregulation of mRNA expression of PPARa/LXRa and ABCA1/G1 after NNK/CS exposure, but future studies (such as miRNA analysis) are required.…”
Section: Discussionmentioning
confidence: 99%